DNA STRUCTURAL CHANGES DURING INTERACTION WITH METAL IONS ON IR- SPECTROSCOPY DATA - Kornilova, S. V. (Biophysical Bulletin)
The metal (Mn-+ ,Mg2+ ,Ca2+ ,Cu 2+ ) ion effect on the DNA structure in films is studied at different relative humidities (5-98%) by the IR-spectroscopy method. The results obtained evidence the interaction of the ions with DNA phosphate groups as well as with nucleic bases. The formation of the secondary structure of DNA eomplexed with metal ions is shown to take place at the greater number of water molecules bound to the polymer than in the case of DNA without ions. The interaction of DNA with metal ions prevents its transition into A-form and induces essential changes in the hydrate water of the complexes. The models for the ion interaction with DNA macromolecules and its components are discussed. Keywords: DNA structure, metal ions, vibration spectroscopy